CRISPR/Cas12a-Mediated Gene Editing in Geodia barretti Sponge Cell Culture - Hesp, Kylie; Flores Alvarez, John L.; Alexandru, Ana-Maria; van der Linden, Jip; Martens, Dirk E.; Wijffels, Rene H.; Pomponi, Shirley A. (Frontiers in Marine Science, 2020)
Sponges and sponge-derived microbes are the most prolific source of marine natural products, and many attempts have been made at creating a marine sponge cell line to produce such products. However, lacking insight in which nutrients sponge cells require to grow and poor genetic accessibility have hampered progress towards this goal. Recently, a new sponge-specific nutrient medium M1 has been shown to stimulate sponge cells to divide rapidly in vitro. In this study we demonstrate for the first time that sponge cells growing in M1 can be genetically modified using a CRISPR/Cas12a gene editing system. The 2',5'-oligoadenylate synthetase gene of cells from the boreal deep-sea sponge Geodia barretti was disrupted, by inserting a short sequence of scrambled DNA using a single-stranded oligodeoxynucleotide donor template. Blue fluorescent marker gene TagBFP was inserted in an intron of the same gene and expressed by G. barretti cells. This shows that CRISPR/Cas12a can be used to disrupt and overexpress genes in sponge cells and represents an important step towards developing an optimized continuous sponge cell line to produce bioactive compounds.